Incidence of cardiovascular events and mortality in Korean patients with chronic kidney disease - Hyunjin Ryu (Nature Portfolio, 2021)
Abstract Few studies have investigated the incidence of cardiovascular disease (CVD) in the Asian chronic kidney disease (CKD) population. This study assessed the incidence of CVD, death, and a composite outcome of CVD and death in a prospective Korean predialysis CKD cohort. From a total of 2179 patients, incidence rates were analyzed, and competing risk analyses were conducted according to CKD stage. Additionally, incidence was compared to the general population. During a median 4.1 years of follow-up, the incidence of CVD, all-cause death, and the composite outcome was 17.2, 9.6, and 24.5 per 1000 person-years, respectively. These values were higher in diabetic vs. non-diabetic subjects (P < 0.001). For all outcomes, incidence rates increased with increasing CKD stage (CVD, P = 0.001; death, P < 0.001; and composite, P < 0.001). Additionally, CKD stage G4 [hazard ratio (HR) 2.8, P = 0.008] and G5 (HR 5.0, P < 0.001) were significant risk factors for the composite outcome compared to stage G1 after adjustment. Compared to the general population, the total cohort population (stages G1–G5) showed significantly higher risk of CVD (HR 2.4, P < 0.001) and the composite outcome (HR 1.7, P < 0.001). The results clearly demonstrate that CKD is a risk factor for CVD in an Asian population.